Design Analysis and Optimization of a Planar Compliant Micro-positioning Stage - Gui Heli; Xu Weisheng; Xu Tianqi; Cao Yi (Jixie chuandong)
In order to design a flexible micro positioning platform with good static and dynamic characteristics, two types of flexible kinematic pairs based on flexible modules composed of flexible beams and circular flexible hinges were proposed. Firstly, a novel planar two degrees of freedom micro positioning platform structure was designed based on the motion pair; secondly, a theoretical model of the platform's force-displacement relation and output displacement was established using the flexibility matrix method, and a theoretical model of the platform's natural frequency and instantaneous dynamic response was established based on the transfer matrix method; then, the correctness of the theoretical model was verified through finite element simulation. Theoretical research and simulation verification show that the platform has high static and dynamic performance, its input and output are fully decoupled, and the loss of motion does not exceed 1.8% under 0.3 mm input displacement; the first order natural frequency is 320.34 Hz, and the dynamic response is consistent with the simulation trend within 0.1 s. Finally, sensitivity analysis and parameter optimization of the static and dynamic performance of the platform were performed. The results show that the optimized platform has improved motion loss and natural frequency optimization by 1.95% and 43.9% respectively under the same drive, further improving the dynamic performance of the platform.